An Overview of Statutes Relating to Civil Procedure in South Africa in Light of the Changes in Technology - Nombulelo Queen Mabeka; Rushiella Songca (Obiter, 2021)
E-technology has fast become an acceptable and convenient method of communication and a prerequisite of business transactions globally. South Africa is no exception to the trend. While technological progress has facilitated rapid change in the way humans communicate and transact, South African law has not kept abreast of the swift transformation and growth in this sector. This lacuna is especially evident in the South African law of civil procedure, which regulates the civil process in South African courts. Although subject to regular amendment, it appears prima facie not to embrace advances in e-technology and their effect – or potential effect – on the legal process. Moreover, the existing corpus of legislation governing civil process appears to have disregarded the provisions of the Electronic Communications and Transactions Act (ECTA) to the extent that it already provides mechanisms for the use of e-technology. In South Africa, the law of civil procedure is regulated by statutes such as the Rules Board for Courts of Law Act, the Superior Courts Act, the Magistrates’ Courts Act, the Sheriffs Act, the National Credit Act, the Small Claims Court Act, and the Divorce Act, which inter alia regulate court process and ensure the fair administration of justice. The submission made here explores this indicated gap within selected legislation pertinent to civil procedure and postulates the effect of e-technology in the context of the abovementioned legislation. As an example, section 35 of the Superior Courts Act indicates that parties and witnesses must make a physical appearance in the court of issue. This provision, however, does not expressly allow for the use of video conferencing, which would enable witnesses to give evidence via e-technology, and thus allow parties to investigate and re-examine witnesses situated in any geographical location outside of court. Further, section 74Q of the Magistrates’ Courts Act makes it mandatory for garnishee orders to be served personally or by registered mail. This provision is not in line with developments in e-technology. Email, Facebook, or other digital means of service could facilitate the service of garnishee orders issued by magistrates’ courts more effectively and remove delays posed by slow postal delivery, and also inhibit the prohibitive cost of personal service. With this contribution, select statutory provisions are compared to ECTA provisions and specific e-technology laws so as to determine the extent of the gap in the implementation of e-technology within the sphere of civil process. The authors then provide insights into how the current civil law statutes could be amended in line with selected e-technology legislation discussed here.